Injectable Thermoresponsive Microparticle/Hydrogel System with Superparamagnetic Nanoparticles for Drug Release and Magnetic Hyperthermia Applications - Carrelo, Henrique (2023)
This work is funded by National Funds through the FCT—Fundação para a Ciência e a Tecnologia, I.P., under the scope of the projects UID/50025/2020-2023 and LA/0037/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication-i3N. This study was also financially supported by MCIN/AEI/10.13039/501100011033///FEDER, UE, through project PID2021-124294OB-C21. Publisher Copyright: © 2023 by the authors.